PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS MEDIA KUIS DALAM MATA PELAJARAN MATEMATIKA KELAS III DI SEKOLAH DASAR NEGERI 3 SEBATU - purnama sari, ayu; Kusuma, Ni Wayan Sri Prabawati (UHN IGB Sugriwa Denpasar, 2025)
Implementation of a Problem Based Learning (PBL) approach integrated with interactive quizzes in mathematics lessons on whole numbers and place value for third-grade students at SD Negeri 3 Sebatu. The main problems identified included students' limited mastery of the concept of positional value in whole numbers, traditional teaching practices, and limited use of engaging learning media. The research methodology employed a descriptive qualitative approach through case studies. The study took place at SD Negeri 3 Sebatu on July 23, 2025, with 20 third-grade students participating. Data were collected through lesson observations, interviews with teachers and students, and documentation of learning outcomes. The research instruments included student activity observation sheets, a rubric for assessing conceptual understanding, and a questionnaire assessing student responses to the learning media. The findings indicate that the implementation of the Problem Based Learning model integrated with quizzes yielded encouraging results achievement of the target. Students demonstrated significant improvements in learning enthusiasm and active participation, along with improved mastery of the concepts of whole numbers and place value. The interactive quizzes proved effective in increasing student engagement and providing direct learning evaluation. This learning approach successfully transformed the learning process from teacher-centered to student-centered, enhancing analytical thinking, problem-solving, and collaboration skills among students. Benefits of this implementation include increased student active participation, mastery of abstract concepts through contextual problems, and the creation of a fun learning atmosphere. Suggestions for future research include the need for comprehensive training for educators in developing contextual Problem Based Learning problems and developing quizzes with a wider variety of media to accommodate students' diverse learning styles.